A Critical Review of “The Ghaznavid and Seljuq Turks: Poetry as a Source for Iranian History” - Yazdan Farrokhi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The aim of this article is to critically review “The Ghaznavid and Seljuq Turks: Poetry as a Source for Iranian History”. Using Farrokhi and Mo῾zziʼs poem as the historical source for Ghaznavid and Seljuq period is the fundamental aim of this book and its advantage beside the historiography source. So, the present article tries to answer such questions: How much the writer of this book succeeds to cover that aim? And, to what extent has it applied the scientific methods properly?Through a critical lens and analytical view, it will prove that this valuable study covers its objective, but it neglects methodological points, and writing instruments; besides, some references and argumentations in few parts of this book are under the question.